Adhesive film and decorative film

The adhesive film with a polyvinyl chloride base layer and (meta) acrylic copolymer adhesive layer, combined with grooves, addresses the issue of gasoline transmission in polyolefin-based resin materials by maintaining adhesion and appearance, enhancing gasoline resistance.

JP7623859B2Active Publication Date: 2025-01-29NIPPON CARBIDE KOGYO KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021041735
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-15
Publication Date
2025-01-29
Estimated Expiration
2041-03-15

AI Technical Summary

Technical Problem

Polyolefin-based resin materials used in fuel tanks and pipes for motorcycles are prone to gasoline transmission, leading to adhesive film swelling and reduced adhesion due to gasoline exposure, which affects the appearance and adhesive strength.

Method used

An adhesive film with a base layer made of polyvinyl chloride resin and an adhesive layer composed of (meta) acrylic copolymer, adhesive resin, and crosslinking agent, featuring grooves on the back surface to dissipate gasoline, ensuring high gasoline resistance and maintaining adhesion.

Benefits of technology

The adhesive film maintains a good appearance and adhesive strength even after exposure to gasoline, preventing swelling and ensuring effective adhesion to polyolefin-based resin surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623859000004
    Figure 0007623859000004
  • Figure 0007623859000005
    Figure 0007623859000005
  • Figure 0007623859000006
    Figure 0007623859000006
Patent Text Reader

Abstract

To provide an adhesive film that maintains a good appearance even after exposed to gasoline.SOLUTION: An adhesive film (100) contains polyvinyl chloride resin in a substrate layer (10). The adhesive layer (20) has a groove (21) on a face disposed back to back with the substrate layer (10). The gasoline permeation at 23°C and 50% RH is 15 g / m2 h or more. The adhesion after exposed to gasoline vapor for two hours at 23°C and 50% RH is 10.0 N / 25 mm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive film and a decorative film. [Background technology]

[0002] Conventionally, methods for decorating the surface of an article such as an exterior part of a vehicle include a method of decorating an adhesive film attached to the surface of the article, and a method of attaching a decorative film in which an adhesive film and a decoration are integrated to the article. In recent years, resins have become mainstream as materials for exterior parts from the viewpoints of light weight, processability, cost, etc. In particular, exterior parts made of polyolefin resins are widely used from the viewpoints of light weight, processability, production cost, etc.

[0003] However, since polyolefin-based resins have low polarity, exterior parts made of polyolefin-based resins are often difficult to adhere to, and therefore pressure-sensitive adhesive films and decorative films to be attached to these exterior parts are required to have high adhesive strength to polyolefin-based resin adherends.

[0004] As an adhesive film for adhering to such polyolefin resin adherends, there is known an adhesive sheet having an adhesive layer made from an adhesive composition containing a (meth)acrylic copolymer, a rosin-based tackifier resin having a softening point of 100°C or higher, and a crosslinking agent (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-177902 A Summary of the Invention [Problem to be solved by the invention]

[0006] Fuel tanks, fuel pipes and other fuel devices provided on racing motorcycles and the like are often made of polyethylene from the viewpoints of light weight and strength. However, polyethylene is easily permeable to gasoline, a type of fuel, and an adhesive film attached to the surface of a polyethylene fuel device that holds gasoline may be exposed to gasoline that has permeated the fuel device. The adhesive sheet described in Patent Document 1 has a problem in that, when exposed to gasoline, the adhesive of the adhesive sheet is likely to dissolve in gasoline and lose its adhesive strength, and in addition, the adhesive sheet is likely to swell due to the permeated gasoline, damaging its appearance.

[0007] In other words, the present invention has been made in consideration of the above problems, and an object of the present invention is to provide an adhesive film and related technology that can maintain a good appearance even after exposure to gasoline. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive film comprising a base layer and a pressure-sensitive adhesive layer formed on at least one surface of the base layer, the base layer containing a polyvinyl chloride resin, the pressure-sensitive adhesive layer being formed from a pressure-sensitive adhesive composition containing a (meth)acrylic copolymer (A), a tackifier resin (B) and a crosslinking agent (C), the pressure-sensitive adhesive layer having a groove on a surface facing away from the base layer, the depth of the groove being smaller than the thickness of the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive film having a gasoline permeation amount of 15 g / m under an atmosphere of 23° C. and 50% RH. 2 ·h or more, and the adhesive strength of the pressure-sensitive adhesive layer after being attached to a polyolefin resin adherend and exposed to gasoline vapor for 2 hours in an atmosphere of 23°C and 50% RH is 10.0 N / 25 mm or more. Effect of the Invention

[0009] According to the present invention, it is possible to provide a pressure-sensitive adhesive film that can maintain a good appearance even after exposure to gasoline, and related techniques thereof. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a diagram showing a schematic cross section of an adhesive film 100 according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a diagram showing a schematic view of the appearance of an adhesive film 100 according to one embodiment of the present invention, viewed from the adhesive layer 20 side to the base layer 10 side. [Diagram 3] FIG. 1 is a diagram showing a schematic cross section of an adhesive film 101 according to one embodiment of the present invention. [Figure 4] 1 is a diagram showing a schematic cross section of a decorative film 200 according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] In this specification, the numerical range indicated using "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In addition, in this specification, when "%" is simply stated, the statement means "% by weight" unless otherwise specified.

[0012] In this specification, "(meth)acrylic" means one or both of acrylic and methacrylic. In addition, in this specification, "(meth)acrylic acid" means one or both of acrylic acid and methacrylic acid. In addition, in this specification, "(meth)acrylate" means one or both of acrylate and methacrylate.

[0013] <Adhesive film 100> When an adhesive film is attached to an adherend that holds gasoline, the adhesion between the adherend and the adhesive film may be lost after a certain period of time, causing the adhesive film to appear swollen. Hereinafter, this appearance of swelling of the adhesive film may be referred to as "gasoline blistering." The present inventors have found that the causes of gasoline blistering are (1) a low gasoline permeation amount in the adhesive film, and (2) a decrease in adhesive strength due to dissolution of the adhesive layer of the adhesive film in gasoline that has permeated the adherend.

[0014] The adhesive film 100 according to one embodiment of the present invention has a high gasoline permeability due to the physical properties and layer structure described below. Therefore, when the adhesive film is exposed to gasoline, gasoline is suitably dispersed, making gasoline blistering unlikely to occur. This allows a good appearance to be maintained. In addition, the adhesive film 100 is unlikely to lose its adhesive strength due to the adhesive layer 20 dissolving in gasoline. This also allows the adhesive film 100 to maintain a good appearance and good adhesive strength. Hereinafter, in this specification, the fact that gasoline blistering is unlikely to occur may be referred to as having high "gasoline blister resistance," and the fact that the adhesive layer 20 is unlikely to lose its adhesive strength due to dissolving in gasoline may be referred to as having high "gasoline resistance."

[0015] The physical properties and then layer structure of the pressure-sensitive adhesive film 100 according to one embodiment of the present invention will be described below.

[0016] [Physical properties of adhesive film 100] The physical properties of the adhesive film 100 will be described in detail below.

[0017] (Gasoline permeation amount) The gasoline permeation amount of the adhesive film 100 under an atmosphere of 23°C and 50% RH (relative humidity) is 15 g / m 2 ·h or more. The gasoline permeation amount means the weight of gasoline that permeates the adhesive film 100 per unit area per hour. 2 By having a permeability of 100 / sq.m. or more, gasoline that has permeated the adherend can easily permeate the adhesive film 100 as well, and even if the film is exposed to gasoline while attached to the adherend, the occurrence of blisters due to the gasoline can be prevented. This allows the adhesive film 100 to dissipate gasoline that can dissolve the adhesive layer 20 from the adhesive layer 20. Therefore, the adhesive film 100 has improved resistance to gasoline blisters and can maintain a good appearance even after exposure to gasoline. From the viewpoint of further improving resistance to gasoline blisters, the gasoline permeation amount of the adhesive film 100 in an atmosphere of 23°C and 50% RH (relative humidity) is preferably 17 g / m.2 h or more, more preferably 20 g / m 2 ·h or more.

[0018] The upper limit of the gasoline permeation amount of the PSA film 100 under an atmosphere of 23°C and 50% RH (relative humidity) is not particularly limited from the viewpoint of further improving gasoline blister resistance. The gasoline permeation amount is preferably 50 g / m2 from the viewpoint of preventing excessive impairment of the mechanical strength of the PSA film 100. 2 h or less, and more preferably 40 g / m 2 ·h or less.

[0019] The gasoline permeation amount of the PSA film 100 in an atmosphere of 23°C and 50% RH (relative humidity) can be measured by a method known in the art. For example, the gasoline permeation amount can be calculated by adding gasoline to a moisture permeable cup, covering the opening of the moisture permeable cup with the PSA film 100, and then recording the change over time in the weight of the moisture permeable cup that is left standing in an atmosphere of 23°C and 50% RH (relative humidity). For example, the gasoline permeation amount can be calculated using the following formula (1). Gasoline permeation rate (g / m 2 ·h)=(M1-M2) / (S·T) Formula (1) In formula (1), M1(g) is the weight of the moisture permeable cup immediately after the adhesive film 100 is attached, M2(g) is the weight of the moisture permeable cup after a predetermined time T(h) has elapsed after the adhesive film 100 is attached, and S(m 2 ) is the opening area of ​​the moisture permeable cup. The evaluation of the gasoline permeation amount also serves as an accelerated test to evaluate the gasoline swelling resistance of the adhesive film against gasoline.

[0020] (Adhesion before exposure to gasoline) The adhesive strength of the adhesive film 100 before exposure to gasoline means the force required to peel off a 25 mm wide portion of the adhesive film 100 that has been left to stand for 48 hours in an atmosphere of 23°C and 50% RH after being attached to an adherend. From the viewpoint of favorably fixing the adhesive state between the adherend and the adhesive film 100, the adhesive strength is preferably 10.0 N / 25 mm or more, and more preferably 12.0 N / 25 mm or more.

[0021] The upper limit of the adhesive strength of the adhesive film 100 before exposure to gasoline is not particularly limited from the viewpoint of fixing the adhesive state between the adherend and the adhesive film 100. From the viewpoint of facilitating repositioning of the adhesive film 100, the adhesive strength is preferably 20.0 N / 25 mm or less, and more preferably 15.0 N / 25 mm or less.

[0022] The adhesive strength of the PSA film 100 before exposure to gasoline can be measured by or using a method known in the art. For example, the adhesive strength can be measured by JIS Z 0237:2009 or a method conforming thereto. For details, see the Examples section.

[0023] (Adhesion after exposure to gasoline) The adhesive strength of the adhesive film 100 after exposure to gasoline means the force required to peel off a 25 mm wide portion of the adhesive film 100 that has been left at rest for 48 hours at 23°C and 50% RH, then for 2 hours at 23°C, 50% RH and gasoline vapor, and then for 30 minutes at 23°C and 50% RH. The adhesive strength is 10.0 N / 25 mm or more. This allows the adhesive film 100 to maintain good adhesive strength to the adherend even after exposure to gasoline. The adhesive strength of the adhesive film 100 after exposure to gasoline is preferably 12.0 N / 25 mm or more, more preferably 14.0 N / 25 mm or more, from the viewpoint of maintaining the adhesive state between the adherend and the adhesive film 100 and maintaining a good appearance.

[0024] From the viewpoint of maintaining a good appearance, there is no particular upper limit to the adhesive strength of the adhesive film 100 after exposure to gasoline. From the viewpoint of facilitating repositioning of the adhesive film 100, the adhesive strength is preferably 20.0 N / 25 mm or less, and more preferably 15.0 N / 25 mm or less.

[0025] The adhesive strength of the adhesive film 100 after exposure to gasoline can be measured by the same method as the adhesive strength before exposure to gasoline described above. For details, see the Examples section.

[0026] [Layer structure of adhesive film 100] The adhesive film 100 having the above-mentioned physical properties can be realized by the layer structure described below.

[0027] Hereinafter, the layer structure of an adhesive film 100 according to one embodiment of the present invention will be described in detail with reference to Fig. 1 and Fig. 2. Fig. 1 is a diagram showing a schematic cross section of an adhesive film 100 according to one embodiment of the present invention. As shown in Fig. 1, the adhesive film 100 comprises a base layer 10 and an adhesive layer 20 formed on at least one surface of the base layer 10. Fig. 2 is a diagram showing a schematic appearance of the adhesive film 100 according to one embodiment of the present invention as viewed from the adhesive layer 20 side to the base layer 10 side.

[0028] (Base material layer 10) The pressure-sensitive adhesive film 100 includes a base layer 10. The base layer 10 is a layer that mainly functions to increase the mechanical strength and weather resistance of the pressure-sensitive adhesive film 100.

[0029] The substrate layer 10 contains a polyvinyl chloride resin. More specifically, the substrate layer 10 is formed from a substrate composition containing a polyvinyl chloride resin. Polyvinyl chloride resins are excellent in mechanical strength and weather resistance, and have the property of easily permeating gasoline. Therefore, by the substrate layer 10 containing a polyvinyl chloride resin, the mechanical strength, weather resistance, and gasoline permeation amount of the PSA film 100 can be increased.

[0030] Examples of polyvinyl chloride resins contained in the substrate composition include: homopolymers of vinyl chloride; copolymers containing vinyl chloride as a structural unit, and polymers in which the structural units of the copolymers are further chlorinated; polymers in which one or more hydrogen atoms of the structural units of polyolefins or polydiene are chlorinated; and other resins. These polyvinyl chloride resins may be contained alone or in a mixture of two or more. Examples of other structural units contained in copolymers containing vinyl chloride as a structural unit include: α-olefins such as ethylene, propylene, and butylene; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as butyl vinyl ether and cetyl vinyl ether; alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate; aromatic vinyls such as styrene and α-methylstyrene; N-substituted maleimides such as N-phenylmaleimide and N-cyclohexylmaleimide; and the like. These other structural units may be contained alone or in a mixture of two or more. More specifically, examples of polyvinyl chloride resins include polyvinyl chloride, polychlorinated vinyl chloride, polyvinylidene chloride, chlorinated polyethylene, vinyl chloride-vinyl acetate copolymer, vinyl chloride-ethylene copolymer, and chloroprene rubber.

[0031] The polyvinyl chloride resin contained in the substrate composition preferably contains a plasticizer. The content of the plasticizer contained in the polyvinyl chloride resin is preferably high from the viewpoint of increasing the gasoline permeation amount of the adhesive film 100, and is preferably 15 parts by weight or more, more preferably 20 parts by weight or more, per 100 parts by weight of the polyvinyl chloride resin. In addition, the content is preferably low from the viewpoint of increasing the mechanical strength and weather resistance of the adhesive film 100, and is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, per 100 parts by weight of the substrate composition.

[0032] Examples of the plasticizer include polyester-based plasticizers, such as phthalate-based plasticizers such as dioctyl terephthalate (DOP) and diisononyl terephthalate (DINP), aromatic polyester-based plasticizers such as trimellitate-based plasticizers, and fatty acid polyester-based plasticizers such as adipate. Other examples of the plasticizer include paraffin-based mineral oil softeners, liquid paraffin, polybutene, etc. These plasticizers may be selected as appropriate.

[0033] The substrate composition forming the substrate layer 10 may contain other components in addition to the polyvinyl chloride resin and plasticizer described above, as long as the effects of the present invention are not impaired. The other components can be appropriately determined depending on the application of the PSA film 100. Examples of the other components include pigments, dispersants, heat stabilizers, fillers, ultraviolet absorbers, and processing aids.

[0034] The thickness L1 of the base layer 10 may be uniform along the entire base layer 10, or may be different for each region within a range that does not impair the effects of the present invention, and can be appropriately determined according to the use of the adhesive film 100. The thickness L1 of the base layer 10 is preferably thicker from the viewpoint of increasing the mechanical strength and weather resistance of the adhesive film 100, and is preferably 20 μm or more, and more preferably 25 μm or more. The thickness L1 of the base layer 10 is preferably thinner from the viewpoint of increasing the gasoline permeation amount of the adhesive film 100, and is preferably 40 μm or less, and more preferably 35 μm or less. The thickness L1 of the base layer 10 may be measured by a low-pressure thickness measuring device under an atmosphere of 23 ° C. and 50% RH. That is, the thickness L1 of the base layer 10 is preferably the above-mentioned preferred thickness as the average thickness of the base layer 10 in the adhesive film cut out as a label, for example.

[0035] The shape of the base material layer 10 can be appropriately determined depending on the application of the adhesive film 100. The shape of the base material layer 10 may be, for example, a flat shape or a curved shape. From the viewpoint of adhering the adhesive film 100 to the adherend over a wider area, the shape of the base material layer 10 is preferably a shape that allows it to be adhered to the adherend without wrinkling.

[0036] (Adhesive layer 20) The adhesive film 100 includes an adhesive layer 20 formed on at least one surface of a base layer 10. The adhesive layer 20 is a layer that mainly has the function of increasing the adhesiveness of the adhesive film 100 to an adherend.

[0037] The pressure-sensitive adhesive layer 20 is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic copolymer (A), a tackifier resin (B), and a crosslinking agent (C). The pressure-sensitive adhesive composition is a liquid, paste, or powder composition, and refers to the composition in a state before a crosslinked structure is constructed by the crosslinking agent (C). The pressure-sensitive adhesive layer 20 is a solid or gel layer, and refers to the layered composition in a state after a crosslinked structure is constructed by the crosslinking agent (C).

[0038] The (meth)acrylic copolymer (A) contained in the pressure-sensitive adhesive composition is preferably a copolymer containing a structural unit derived from a (meth)acrylic acid monomer (A-1) and an alkyl (meth)acrylate monomer (A-2) having a glass transition temperature of -60°C or lower. The (meth)acrylic copolymer (A) may also contain a (meth)acrylate monomer (A-3). The (meth)acrylic copolymer (A) exhibits good adhesion to polyolefin resin adherends and is suitable for gasoline permeation. Therefore, the (meth)acrylic copolymer (A) is suitable as a material for the pressure-sensitive adhesive layer 20 of the pressure-sensitive adhesive film 100.

[0039] The (meth)acrylic copolymer (A) preferably contains a structural unit derived from a (meth)acrylic acid monomer (A-1). In this specification, the (meth)acrylic acid monomer (A-1) includes a monomer having a carboxyl group, such as (meth)acrylic acid, and an unsaturated double bond group capable of radical polymerization. Examples of the (meth)acrylic acid monomer (A-1) include (meth)acrylic acid and carboxyl group-containing (meth)acrylic acid derivatives. Examples of the carboxyl group-containing (meth)acrylic acid derivatives include crotonic acid, fumaric acid, itaconic acid, glutaconic acid, and citraconic acid. The (meth)acrylic acid monomer (A-1) and the alkyl (meth)acrylate monomer (A-2) can be distinguished from each other by whether or not the carboxyl group of the (meth)acrylic acid monomer (A-1) is ester-bonded.

[0040] The content of the structural unit derived from the (meth)acrylic acid monomer (A-1) contained in the (meth)acrylic copolymer (A) is preferably 5 parts by weight or more, more preferably 6 parts by weight or more, based on 100 parts by weight of the (meth)acrylic copolymer (A). The higher the content of the structural unit derived from the (meth)acrylic acid monomer (A-1), the higher the amount of carboxyl functional groups in the adhesive composition and the higher the cohesive force of the adhesive composition, thereby improving the gasoline resistance. In addition, the content of the structural unit derived from the (meth)acrylic acid monomer (A-1) contained in the (meth)acrylic copolymer (A) is preferably 10 parts by weight or less, more preferably 8 parts by weight or less, based on 100 parts by weight of the (meth)acrylic copolymer (A). This allows the adhesive layer 20 to be softened, and the adhesiveness of the adhesive film 100 to the adherend can be improved while providing gasoline blister resistance.

[0041] The (meth)acrylic copolymer (A) preferably contains a structural unit derived from an alkyl (meth)acrylate monomer (A-2) having a glass transition temperature of -60°C or less. The structural unit derived from an alkyl (meth)acrylate monomer (A-2) having a glass transition temperature of -60°C or less means a structural unit of an alkyl (meth)acrylate monomer having a glass transition temperature of -60°C or less in a homopolymer of the structural unit. The structural unit contributes to lowering the glass transition temperature of the (meth)acrylic copolymer (A) more than the structural unit derived from a (meth)acrylic acid monomer (A-1) and the structural unit derived from a (meth)acrylate monomer (A-3) described later. In this specification, the term "alkyl (meth)acrylate monomer" includes the meaning of a (meth)acrylate monomer having at least a partial alkyl chain and the meaning of an alkyl (meth)acrylate monomer having a functional group such as a hydroxyl group in addition to an alkyl chain.

[0042] By including in the (meth)acrylic copolymer (A) a structural unit derived from an alkyl (meth)acrylate monomer (A-2) having a glass transition temperature of -60°C or lower, the glass transition temperature of the (meth)acrylic copolymer (A) can be suitably lowered, and the adhesiveness of the pressure-sensitive adhesive film 100 to a polyolefin adherend can be further improved. Examples of monomers for obtaining structural units derived from an alkyl (meth)acrylate monomer (A-2) having a glass transition temperature of -60°C or lower include isodecyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and lauryl (meth)acrylate. Furthermore, examples of monomers for obtaining structural units derived from alkyl (meth)acrylate monomers (A-2) having a glass transition temperature of -60°C or lower include alkyl (meth)acrylates having a hydroxyl group, such as polypropylene glycol mono(meth)acrylate, pentaerythritol tri(meth)acrylate, methoxypolyethylene glycol (350) mono(meth)acrylate, and methoxypolyethylene glycol (550) mono(meth)acrylate. In the (meth)acrylic copolymer (A), the structural units derived from the alkyl (meth)acrylate monomers (A-2) may be contained alone or in a mixture of two or more kinds.

[0043] The content of the structural unit derived from the alkyl (meth)acrylate monomer (A-2) contained in the (meth)acrylic copolymer (A) is preferably 20 parts by weight or more, more preferably 25 parts by weight or more, relative to 100 parts by weight of the (meth)acrylic copolymer (A). This can further improve the adhesion of the adhesive film 100 to the adherend. In addition, the content of the structural unit derived from the alkyl (meth)acrylate monomer (A-2) contained in the (meth)acrylic copolymer (A) is preferably 40 parts by weight or less, more preferably 30 parts by weight or less, relative to 100 parts by weight of the (meth)acrylic copolymer (A). The smaller the content, the better the cohesive force of the adhesive composition, and the better the gasoline resistance of the adhesive film 100.

[0044] In addition, the (meth)acrylic copolymer (A) may contain a structural unit derived from a (meth)acrylate monomer (A-3) other than the structural unit derived from the (meth)acrylic acid monomer (A-1) and the structural unit derived from the alkyl (meth)acrylate monomer (A-2).

[0045] The structural unit derived from the (meth)acrylate monomer (A-3) means a structural unit of a (meth)acrylate monomer having a glass transition temperature of higher than -60°C in a homopolymer of the structural unit. The structural unit contributes to raising the glass transition temperature of the (meth)acrylic copolymer (A) more than the structural unit derived from the (meth)acrylic acid monomer (A-1) and the structural unit derived from the above-mentioned (meth)acrylate monomer (A-2). By including the structural unit derived from the (meth)acrylate monomer (A-3) in the (meth)acrylic copolymer (A), cohesion can be imparted and a decrease in adhesive strength after exposure to gasoline can be suppressed. Examples of monomers for obtaining structural units derived from the (meth)acrylate monomer (A-3) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, isobornyl (meth)acrylate, 2-methoxy (meth)acrylate, 2-ethoxy (meth)acrylate, glycidyl (meth)acrylate, and tetrahydrofurfuryl (meth)acrylate. Furthermore, examples of monomers for obtaining structural units derived from the (meth)acrylate monomer (A-3) include (meth)acrylates having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 3-methyl-3-hydroxybutyl (meth)acrylate, 1,3-dimethyl-3-hydroxybutyl (meth)acrylate, 2,2,4-trimethyl-3-hydroxypentyl (meth)acrylate, 2-ethyl-3-hydroxyhexyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and poly(ethylene glycol-propylene glycol) mono(meth)acrylate.Among them, the monomer for obtaining the structural unit derived from the (meth)acrylate monomer (A-3) is preferably butyl acrylate from the viewpoint of improving the cohesive strength of the pressure-sensitive adhesive composition. The structural unit derived from the (meth)acrylate monomer (A-3) may be contained alone or in a mixture of two or more kinds.

[0046] In addition, the content of the structural unit derived from the (meth)acrylate monomer (A-3) contained in the (meth)acrylic copolymer (A) is preferably 50 parts by weight or more, and more preferably 65 parts by weight or more, per 100 parts by weight of the (meth)acrylic copolymer (A).A higher content improves the cohesive strength of the adhesive composition, thereby further improving the gasoline resistance of the adhesive film 100.

[0047] In addition, the (meth)acrylic copolymer (A) may contain a monomer copolymerizable with the (meth)acrylic monomer, as long as the effect of the present invention is not impaired. Examples of the copolymerizable monomer include vinyl esters such as vinyl acetate, vinyl ethers, acrylonitrile, acrylamide, and styrene.

[0048] The glass transition temperature of the (meth)acrylic copolymer (A) is preferably -50°C or lower, more preferably -55°C or lower, from the viewpoint of softening the pressure-sensitive adhesive layer 20 and improving the adhesion of the pressure-sensitive adhesive film 100 to an adherend, thereby increasing the adhesive strength. Also, the glass transition temperature of the (meth)acrylic copolymer (A) is preferably -60°C or higher, more preferably -58°C or higher, from the viewpoint of improving the cohesive strength of the pressure-sensitive adhesive composition and thus improving the gasoline resistance, and is preferably set high at -60°C or higher.

[0049] The glass transition temperature of the (meth)acrylic copolymer (A) is calculated according to the glass transition temperature and content of the monomer contained as a constituent unit in the (meth)acrylic copolymer (A). Specifically, the glass transition temperature Tg0 (K) of the (meth)acrylic copolymer (A) containing monomers 1 to n (n is an integer of 2 or more) as constituent units is calculated using the following formula (2). 1 / Tg0=[(W1 / Tg1)+(W2 / Tg2)+···+(W n / Tg n )] / 100 Formula (2) In formula (2), Tg1~Tg n (K) is the glass transition temperature of the first to nth monomers, W1 to W n The (parts by weight) are the contents of the 1st to nth monomers contained in 100 parts by weight of the (meth)acrylic copolymer (A). The glass transition temperature Tg0 (K) of the (meth)acrylic copolymer (A) is determined using absolute temperature (K), but is expressed in degrees Celsius (°C) in this specification. The glass transition temperature Tg i is the temperature of the inflection point of the DSC curve obtained by measurement under the following conditions using a differential scanning calorimeter (DSC) measuring device. Differential scanning calorimetry (DSC) measuring device "EXSTAR6000" (Seiko Instruments Inc.) Atmosphere: Nitrogen flow Amount of sample to be measured: 10mg Heating rate: 10℃ / min

[0050] Representative glass transition temperatures of homopolymers of each structural unit are measured as follows: methyl methacrylate: 103° C., n-butyl methacrylate: 21° C., butyl acrylate: −57° C., 2-hydroxyethyl methacrylate: 55° C., 2-hydroxyethyl acrylate: −15° C., acrylic acid: 166° C., methacrylic acid: 185° C., etc. The glass transition temperatures of these homopolymers are measured by a differential scanning calorimeter (DSC) measuring device, like the (meth)acrylic copolymer (A).

[0051] The weight average molecular weight of the (meth)acrylic copolymer (A) is preferably 80×10 from the viewpoint of improving the cohesive strength of the pressure-sensitive adhesive composition and improving the gasoline resistance. 4 More preferably, it is 100×10 4 The weight average molecular weight of the (meth)acrylic copolymer (A) is preferably 150×10 or more, from the viewpoint of softening the pressure-sensitive adhesive composition and improving the adhesion of the pressure-sensitive adhesive film 100 to an adherend. 4 More preferably, it is 120×10 or less. 4 The smaller the value, the more preferable from the viewpoint of enhancing the gasoline permeability.

[0052] The pressure-sensitive adhesive composition contains a tackifier resin (B), which can further improve the adhesive strength of the pressure-sensitive adhesive composition containing the above-mentioned (meth)acrylic copolymer (A) and can also improve the tackiness.

[0053] Examples of the tackifier resin (B) contained in the pressure-sensitive adhesive composition include natural resin-based tackifier resins and synthetic resin-based tackifier resins. In this specification, these tackifier resins may be referred to as tackifier resins. Examples of the natural resin-based tackifier resins include rosin resins such as rosin, rosin ester, rosin phenol, and colorless rosin derivatives; terpene resins such as terpene, aromatic modified terpene, and terpene phenol; and the like. Examples of the synthetic resin-based tackifier resins include petroleum resins such as aromatic petroleum resins, aliphatic petroleum resins, and alicyclic petroleum resins; styrene-based synthetic resins; phenol-based synthetic resins; xylene-based synthetic resins; ketone-based synthetic resins; and the like. These tackifier resins (B) may be contained alone or in a mixture of two or more.

[0054] The tackifier resin (B) may be a manufactured product or a commercially available product. Examples of commercially available tackifier resins (B) include "FTR6100" (manufactured by Mitsui Chemicals, Inc., "FTR" is a registered trademark of the company), "YS Polystar TH130" (manufactured by Yasuhara Chemical Co., Ltd.), "D-125" (manufactured by Arakawa Chemical Industries, Ltd.), and "Haritac PCJ" (manufactured by Harima Chemical Group, Inc.).

[0055] The content of the tackifier resin (B) contained in the pressure-sensitive adhesive composition is preferably 20 parts by weight or more, more preferably 30 parts by weight or more, per 100 parts by weight of the (meth)acrylic copolymer (A), from the viewpoint of further improving the adhesive strength of the pressure-sensitive adhesive film 100 to an adherend. Also, the content of the tackifier resin (B) contained in the pressure-sensitive adhesive composition is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, per 100 parts by weight of the (meth)acrylic copolymer (A), from the viewpoint of improving the cohesive strength of the pressure-sensitive adhesive composition and improving gasoline resistance, and it is preferable that the content is less than 40 parts by weight.

[0056] The pressure-sensitive adhesive composition contains a crosslinking agent (C). The crosslinking agent (C) contained in the pressure-sensitive adhesive composition may contain one type alone or two or more types in combination.

[0057] The crosslinking agent (C) contained in the pressure-sensitive adhesive composition is preferably an isocyanate-based crosslinking agent from the viewpoint of improving the balance between tackiness and cohesive strength. Examples of the isocyanate-based crosslinking agent include aromatic polyisocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, isocyanate multimers, and isocyanate adducts. Examples of the aromatic polyisocyanates include xylylene diisocyanate (XDI), diphenylmethane diisocyanate (MDI), triphenylmethane triisocyanate, and tolylene diisocyanate (TDI). Examples of the aliphatic polyisocyanates include butane diisocyanate, pentane diisocyanate, hexamethylene diisocyanate (HDI), heptamethylene diisocyanate, trimethylhexamethylene diisocyanate, and lysine diisocyanate. Examples of alicyclic polyisocyanates include isophorone diisocyanate (IPDI), hydrogenated xylylene diisocyanate (hydrogenated XDI), and hydrogenated diphenylmethane diisocyanate (hydrogenated MDI). Examples of isocyanate multimers include isocyanate dimers and trimers. Examples of isocyanate adducts include adducts of isocyanate and polyhydric alcohol or urea compound.

[0058] The isocyanate crosslinking agent may be a manufactured product or a commercially available product. Examples of commercially available isocyanate crosslinking agents include "Coronate L-45E" (manufactured by Tosoh Corporation, "Coronate" is a registered trademark of the company), "Duranate D201" (manufactured by Asahi Kasei Corporation, "Duranate" is a registered trademark of the company), and "Takenate D-127N" (manufactured by Mitsui Chemicals, Inc., "Takenate" is a registered trademark of the company).

[0059] The crosslinking agent (C) contained in the pressure-sensitive adhesive composition may contain other crosslinking agents instead of or in addition to the isocyanate crosslinking agent. Examples of the other crosslinking agents include melamine crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, metal chelate crosslinking agents, organosilane crosslinking agents, epoxy crosslinking agents, and acid anhydride crosslinking agents. The other crosslinking agents may be contained alone or in a mixture of two or more.

[0060] The content of the crosslinking agent (C) contained in the pressure-sensitive adhesive composition is preferably 1.00 parts by weight or more, more preferably 1.25 parts by weight or more, based on 100 parts by weight of the (meth)acrylic copolymer (A) from the viewpoint of improving the cohesive strength of the pressure-sensitive adhesive composition. Also, the content of the crosslinking agent (C) contained in the pressure-sensitive adhesive composition is preferably 2.50 parts by weight or less, more preferably 2.00 parts by weight or less, based on 100 parts by weight of the (meth)acrylic copolymer (A) from the viewpoint of improving tackiness.

[0061] The pressure-sensitive adhesive composition may contain other components in addition to the above-mentioned (meth)acrylic copolymer (A), tackifier resin (B) and crosslinking agent (C) within the scope of not impairing the effects of the present invention. The other components can be appropriately determined depending on the application of the pressure-sensitive adhesive film 100. Examples of the other components include pigments, dispersants, heat stabilizers, plasticizers, fillers, and ultraviolet absorbers.

[0062] The thickness L2 of the pressure-sensitive adhesive layer 20 is preferably 20 μm or more, more preferably 25 μm or more, from the viewpoint of improving the adhesive strength of the pressure-sensitive adhesive film 100 to an adherend. Moreover, the thickness L2 of the pressure-sensitive adhesive layer 20 is preferably 40 μm or less, more preferably 35 μm or less, from the viewpoint of improving the productivity of the pressure-sensitive adhesive film 100.

[0063] The adhesive layer 20 has a groove 21 on the surface facing away from the base layer 10. Due to the presence of the groove 21 on the surface of the adhesive layer 20 facing away from the base layer 10, i.e., the adhesive surface, when the adhesive film 100 is attached to an adherend, a gap is generated between the adherend and the adhesive film 100. As a result, gasoline that has permeated the adherend and reached the adhesive film 100 can dissipate to the outside of the adhesive film 100 through the gap, regardless of whether it is in a gaseous or liquid state. Therefore, gasoline swelling in the adhesive film 100 can be reduced or prevented.

[0064] The depth L3 of the groove 21 is smaller than the thickness L2 of the adhesive layer 20. That is, the groove 21 does not penetrate the adhesive layer 20 and does not reach the base layer 10. This can reduce air bubbles that occur during the production of the adhesive film 100 and cause product defects, and can also reduce the formation of uneven shapes on the surface of the base layer 10 facing the adhesive layer 20. From the viewpoint of more efficient diffusion of gasoline, the depth L3 of the groove 21 is preferably 10 μm or more, more preferably 12 μm or more, and the deeper the better. In addition, the depth L3 of the groove 21 is preferably 20 μm or less, more preferably 18 μm or less, from the viewpoint of making the groove 21 less likely to be blocked and maintaining the function of diffusing gasoline in an appropriate manner.

[0065] The ratio of the depth L3 of groove portion 21 to the width L4 of groove portion 21 is preferably 2:20 to 10:20, and more preferably 3:20 to 8:20. That is, by making the width L4 larger than the depth L3, even if the pressure-sensitive adhesive layer 20 swells with gasoline, groove portion 21 is less likely to be blocked, and the gasoline diffusion function can be suitably maintained. In calculating the above ratio, it is preferable that the width L4 of groove portion 21 is defined as the average width of groove portion 21.

[0066] When the opening of the groove 21 is covered with a flat adherend and cut along a plane perpendicular to the direction in which the groove 21 extends, the cross-sectional area of ​​the flow path formed by the groove 21 and the adherend is preferably 500 μm 2 More preferably, it is 1000 μm or more. 2This provides the PSA film 100 with the function of dissipating gasoline from the flow path formed by the grooves 21 before the PSA layer 20 swells with gasoline. The cross-sectional area of ​​the flow path formed by the grooves 21 and the adherend is, for example, 500 μm, which is the product of the depth L3 and the width L4 of the grooves 21 in FIG. 2 More preferably, it is 1000 μm or more. 2 It is sufficient that the groove 21 has an area of ​​100 mm or more. The cross-sectional shape does not necessarily have to be rectangular, and may be trapezoidal or triangular. When the groove 21 is cut along a plane perpendicular to the direction in which the groove 21 extends, the shape of the inside of the groove 21 may be V-shaped, U-shaped, or the like.

[0067] The arrangement of the grooves 21 in the adhesive layer 20 can be appropriately determined within a range that does not impair the above-mentioned function of the grooves 21. In the adhesive layer 20, the inside of the grooves 21 forming the flow paths may extend vertically and horizontally, in other words, in a square lattice shape, as shown in FIG. 2, or may extend in stripes parallel to the two sides constituting the outer edge of the adhesive layer 20, or may have other arrangements. The inside of the grooves 21 forming the flow paths may be not only a square lattice shape, but also a polygonal lattice shape such as a triangular lattice shape or a hexagonal lattice shape, and a multiple polygonal lattice shape such as a double hexagonal lattice shape. From the viewpoint of more efficiently dissipating gasoline, it is preferable that the grooves 21 reach the outer edge of the adhesive layer 20 at least at one point.

[0068] In addition, it is preferable that 5 to 15 grooves are provided per 1 cm around the entire circumference of the adhesive layer in a plan view, and more preferably 8 to 12 grooves are provided per 1 cm around the entire circumference of the adhesive layer in a plan view. This makes it possible to favorably impart the function of dissipating gasoline from the side surface of the adhesive film, and improves the gasoline blistering resistance of the adhesive film.

[0069] [Uses of adhesive film 100] The adhesive film 100 can be used for various purposes. Examples of the uses of the adhesive film 100 include use in attaching it to an adherend made of a polyolefin resin. Particularly, examples of the uses of the adhesive film 100 include use as an exterior adhesive film for a fuel device made of a polyolefin resin. In this specification, the term "fuel device" refers to an article used in an application where it may come into contact with fuel such as gasoline and diesel. Examples of the fuel device include a fuel tank that stores fuel and a fuel pipe that is a fuel path. In addition, examples of the polyolefin resin, i.e., the material of the adherend, include polyethylene and polypropylene, and examples of polyethylene include high density polyethylene (HDPE).

[0070] Polyolefin resins are sometimes used as materials for fuel devices because of their light weight and high strength. However, polyolefin resins are easily permeable to gasoline, a type of fuel, and gasoline may seep out onto the surface of a polyolefin resin fuel device that holds gasoline. However, the adhesive film 100 has the above-mentioned physical properties and layer structure, making it less likely to cause gasoline blisters and able to maintain a good appearance, as well as maintaining good adhesive strength even after exposure to gasoline.

[0071] <Adhesive Film 101> The adhesive film according to one embodiment of the present invention is not limited to the adhesive film 100 described above. For example, the adhesive film according to one embodiment of the present invention may further have layers other than the base layer and the adhesive layer, as long as the effects of the present invention can be obtained. Hereinafter, the layer structure of the adhesive film 101 according to one embodiment of the present invention having other layers will be described in detail with reference to FIG. 3. FIG. 3 is a schematic diagram showing a cross section of the adhesive film 101 according to one embodiment of the present invention. Note that, in the description of the layer structure of the adhesive film 101, matters that overlap with the description of the layer structure of the adhesive film 100 will be omitted.

[0072] (Release film 30) As shown in Fig. 3, the adhesive film 101 according to one embodiment of the present invention may include a release film 30 as a layer other than the base layer 10 and the adhesive layer 20. The release film 30 has releasability and is a film capable of releasably supporting the adhesive layer 20 included in the adhesive film 101. The release film 30 is peeled off when the adhesive film 101 is used. This exposes the adhesive layer 20, allowing the adhesive film 101 to be attached to an adherend. It is preferable that the adhesive film 101 includes the release film 30 from the viewpoint of maintaining the adhesive force of the adhesive layer 20 in a good condition.

[0073] The release film 30 is preferably capable of engaging with the grooves 21 of the adhesive layer 20 and has ridges 31 extending along the grooves 21. This makes the grooves 21 less likely to become clogged while the adhesive film 101 is stored, and can more suitably reduce gasoline swelling of the adhesive film 101. The height of the ridges 31 of the release film 30 is preferably within a range of 20 μm to 25 μm.

[0074] <Method of manufacturing adhesive film> The adhesive film according to one embodiment of the present invention can be manufactured by a known method capable of arranging a base layer and an adhesive layer in a superposed manner. For example, the manufacturing method of the adhesive film according to one embodiment of the present invention may include: a step (1) of preparing a base layer; a step (2) of forming an adhesive layer; and a step (3) of forming a groove portion.

[0075] The step (1) of preparing the substrate layer may be carried out by purchasing a known substrate as the substrate layer, or by kneading the composition and forming the resulting kneaded product into a substrate layer by a known film-forming method, such as an extrusion method, a calendar method, a sol-casting method, and a melt-casting method.

[0076] The step (2) of forming the adhesive layer may include: a substep (2-1) of applying an adhesive composition to one side of a release film; a substep (2-2) of drying the applied adhesive composition; and a substep (2-3) of attaching a substrate layer to the dried adhesive composition.

[0077] The sub-step (2-1) of applying the adhesive composition may be carried out by a known application method. Examples of the application method include screen printing, gravure printing, bar coating, knife coating, roll coating, comma coating, blade coating, die coating, spray coating, electrostatic coating, and dip coating. In the sub-step (2-1) of applying the adhesive composition, the adhesive composition may contain a known dilution solvent such as ethyl acetate in order to adjust the solid content and facilitate application.

[0078] The sub-step (2-2) of drying the adhesive composition may be, for example, a step of drying the adhesive composition by heating with a known heating device. Examples of known heating devices include an infrared heater, a hot air dryer, an oven, or a hot plate. In the sub-step (2-2) of drying the adhesive composition, at least one of the evaporation of the diluent contained in the adhesive composition and the crosslinking reaction of the resin and the crosslinking agent contained in the adhesive composition is promoted, and an adhesive layer can be formed. In the sub-step (2-2), the temperature at which the adhesive composition is dried is preferably 80°C to 100°C from the viewpoint of drying the solvent.

[0079] The sub-step (2-3) of attaching a substrate layer to the adhesive composition may be a step of attaching a substrate layer to the dried adhesive composition by a known method such as heat-pressure bonding and lamination, etc. In the sub-step (2-3), the temperature for heat-pressure bonding and lamination is preferably 20° C. to 40° C. from the viewpoint of adhesion between the adhesive composition and the substrate layer.

[0080] Alternatively, the step (2) of forming the adhesive layer may include, instead of the above-mentioned substeps (2-1), (2-2), and (2-3), a substep (2-1') of applying an adhesive composition to one side of the base layer; and a substep (2-2') of drying the applied adhesive composition, and may optionally further include a substep (2-3') of attaching a release film to the dried adhesive composition. The substeps (2-1'), (2-2'), and (2-3') may be performed by exchanging the base layer and the release film in the above-mentioned substeps (2-1), (2-2), and (2-3).

[0081] The step (3) of forming the grooves can be carried out by a known method for providing grooves in a pressure-sensitive adhesive layer formed by a pressure-sensitive adhesive composition. When the step (2) of forming the pressure-sensitive adhesive layer includes a substep (2-1) of applying the pressure-sensitive adhesive composition to one side of a release film, for example, a release film having an extending ridge may be used in the substep (2-1), and then the substeps (2-2) and (2-3) may be carried out to form the grooves. This makes it possible to obtain a pressure-sensitive adhesive layer having grooves having a shape that can be engaged with the shape of the ridges of the release film. When the step (2) of forming the pressure-sensitive adhesive layer includes a substep (2-1') of applying the pressure-sensitive adhesive composition to one side of a base layer, for example, the grooves may be formed by etching the dried pressure-sensitive adhesive composition by a known method after the substep (2-2').

[0082] The method for producing a pressure-sensitive adhesive film according to one embodiment of the present invention may include, after the above-mentioned steps (1) to (3), a step (4) of leaving the pressure-sensitive adhesive film to stand for 4 to 7 days in an atmosphere at 23° C. to 40° C. before attaching the pressure-sensitive adhesive film to an adherend, which allows the acrylic copolymer and the crosslinking agent contained in the pressure-sensitive adhesive composition to react sufficiently.

[0083] <Decorative Film 200> One aspect of the present invention relates to a decorative film. Hereinafter, the layer structure of a decorative film 200 according to one embodiment of the present invention will be described in detail with reference to Fig. 4. Fig. 4 is a diagram showing a schematic cross section of a decorative film 200 according to one embodiment of the present invention. Note that, among the descriptions of the layer structure of the decorative film 200, matters that overlap with the descriptions of the layer structure of the adhesive film 100 will be omitted.

[0084] (Decorative layer 40) The decorative film 200 is provided with a decorative layer 40 on one side of the base layer 10 of the adhesive film according to one embodiment of the present invention, i.e., on the side (second side) opposite to the side (first side) of the base layer facing the adhesive layer 20. The decorative layer 40 is a layer that mainly has the function of enhancing the design of the decorative film 200.

[0085] The decorative layer 40 is a layer formed from a colorant composition, and is usually formed to realize a desired design. The decorative layer 40 can be formed, for example, from a known ink used in normal printing. The ink may be used alone or in combination of two or more kinds. The ink may contain a colorant that can be used in normal printing. Examples of the colorant include organic pigments, inorganic pigments, and dyes. The colorant may be used alone or in combination of two or more kinds.

[0086] Furthermore, in order to achieve a specific effect in the design of the decorative film 200, a specific pigment may be used as a colorant. An example of the specific pigment is a glittering pigment. An example of the glittering pigment is light-reflective powder particles having a scaly shape. Examples of materials for the powder particles include metals such as aluminum, nickel, copper, gold, silver, tin, titanium, stainless steel, and brass, titanium dioxide-coated mica, basic lead carbonate, shells, and glass.

[0087] Examples of the ink include acrylic ink, urethane ink, polyester ink, vinyl chloride ink, vinyl acetate ink, etc. The ink may be used alone or in combination of two or more kinds.

[0088] The thickness L5 of the decorative layer 40 is preferably 4 μm or more, more preferably 10 μm or more, from the viewpoint of fully expressing the initial design. Also, the thickness L5 of the decorative layer 40 is preferably 30 μm or less, more preferably 25 μm or less, from the viewpoint of increasing the gasoline permeation amount of the decorative film 200.

[0089] <Decorative film according to another embodiment> The decorative film according to one embodiment of the present invention is not limited to the decorative film 200 described above. For example, the decorative film according to another embodiment of the present invention may further have layers other than the base layer, the adhesive layer, and the decorative layer, as long as the effects of the present invention can be obtained. Examples of the other layers include: (1) the release film described above; (2) a surface protection layer that protects the decorative layer; and (3) an adhesive layer for adhering the surface protection layer to the decorative layer.

[0090] When the decorative film has a surface protective layer, the surface protective layer constitutes the surface of the decorative sheet and protects the decorative layer by covering it. From the viewpoint of fully expressing the design of the decorative layer, the surface protective layer preferably has light transmittance and weather resistance. From the viewpoint of gasoline blister resistance, the thickness of the surface protective layer is preferably within the range of 4 to 15 μm, and within the range, the thinner the thickness, the more preferable.

[0091] The surface protective layer can be made of a known resin film having optical transparency. Examples of optically transparent resins that can be used for the surface protective layer include chlorinated polyolefins such as chlorinated polyethylene and chlorinated polypropylene, urethane resins, acrylic resins, vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, and cellulose-based resins, as described in JP 2014-200977 A. From the viewpoint of maintaining gasoline blister resistance, it is preferable that the resin constituting the surface protective layer is a chlorinated polyolefin such as chlorinated polyethylene and chlorinated polypropylene.

[0092] When the surface protective layer is made of a known resin film having light transmittance, the adhesive layer interposed between the surface protective layer and the decorative layer is preferably made of an adhesive composition for forming the adhesive layer of the adhesive film according to one embodiment of the present invention, from the viewpoint of gasoline blister resistance and gasoline resistance. The composition of the adhesive composition is the same as that of the adhesive composition of the adhesive film 100 according to one embodiment of the present invention, so the description thereof is omitted.

[0093] <Method of manufacturing decorative film> The decorative film according to one embodiment of the present invention can be manufactured by a known method capable of arranging a base layer, a pressure-sensitive adhesive layer, and a decorative layer in a layered manner. The manufacturing method of the decorative film according to one embodiment of the present invention can include, for example, a step (5) of forming a decorative layer after the above-mentioned manufacturing method of the pressure-sensitive adhesive film.

[0094] The step of forming the decorative layer may be carried out by applying a colorant composition to the surface of the base layer opposite the pressure-sensitive adhesive layer and drying the applied colorant composition, or by attaching a pre-formed decorative layer to the surface of the base layer opposite the pressure-sensitive adhesive layer.

[0095] <Summary> An adhesive film according to one embodiment of the present invention is an adhesive film comprising a base layer and an adhesive layer formed on at least one surface of the base layer, the base layer containing a polyvinyl chloride resin, the adhesive layer being formed from an adhesive composition containing a (meth)acrylic copolymer (A), a tackifier resin (B) and a crosslinking agent (C), the adhesive layer having a groove on a surface facing away from the base layer, the depth of the groove being smaller than the thickness of the adhesive layer, and the adhesive film having a gasoline permeation amount of 15 g / m under an atmosphere of 23° C. and 50% RH. 2 ·h or more, and the adhesive strength of the adhesive layer after being attached to a polyolefin resin adherend and exposed to gasoline vapor for 2 hours in an atmosphere of 23°C and 50% RH is 10.0 N / 25 mm or more. This makes it possible to provide an adhesive film that can maintain good adhesive strength to a polyolefin resin adherend and good appearance even after exposure to gasoline.

[0096] The (meth)acrylic copolymer (A) of the pressure-sensitive adhesive film according to one embodiment of the present invention comprises a structural unit derived from a (meth)acrylic acid monomer (A-1) and an alkyl (meth)acrylate monomer (A-2) having a glass transition temperature of −60° C. or lower, the content of the structural unit derived from the (meth)acrylic acid monomer (A-1) contained in the (meth)acrylic copolymer (A) is 5 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of the (meth)acrylic copolymer (A), the content of the structural unit derived from the alkyl (meth)acrylate monomer (A-2) contained in the (meth)acrylic copolymer (A) is 20 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the (meth)acrylic copolymer (A), and the weight average molecular weight of the (meth)acrylic copolymer (A) is 80×10 4 That's it, 150 x 10 4 This improves the cohesive strength of the pressure-sensitive adhesive composition, thereby improving the gasoline resistance of the pressure-sensitive adhesive film and also improving the adhesion of the pressure-sensitive adhesive film to an adherend.

[0097] The ratio of the depth of the grooves in the pressure-sensitive adhesive layer of the pressure-sensitive adhesive film according to one embodiment of the present invention to the width of the grooves is preferably 2:20 to 10:20, which allows gasoline to diffuse more efficiently and also maintains the gasoline diffusing function in an optimal manner.

[0098] The content of the tackifier resin (B) contained in the pressure-sensitive adhesive composition of the pressure-sensitive adhesive film according to one embodiment of the present invention is preferably 20 parts by weight or more and 40 parts by weight or less per 100 parts by weight of the (meth)acrylic copolymer (A), which can further improve the adhesive strength of the pressure-sensitive adhesive film to an adherend and can improve the cohesive strength of the pressure-sensitive adhesive composition, thereby improving gasoline resistance.

[0099] The adhesive strength of the pressure-sensitive adhesive film according to one embodiment of the present invention to a polyolefin resin adherend before exposure to gasoline vapor is preferably 10.0 N / 25 mm or more, which allows the adhesive state between the adherend and the pressure-sensitive adhesive film to be favorably fixed.

[0100] The thickness of the pressure-sensitive adhesive layer of the pressure-sensitive adhesive film according to one embodiment of the present invention is preferably 20 μm or more and 40 μm or less, thereby improving the adhesive strength of the pressure-sensitive adhesive film to an adherend and improving the productivity of the pressure-sensitive adhesive film.

[0101] The crosslinking agent (C) of the pressure-sensitive adhesive film according to one embodiment of the present invention is preferably an isocyanate-based crosslinking agent, which can impart appropriate tackiness and cohesive strength to the pressure-sensitive adhesive film.

[0102] The thickness of the base layer of the pressure-sensitive adhesive film according to one embodiment of the present invention is preferably 20 μm or more and 40 μm or less, which can increase the mechanical strength and weather resistance of the pressure-sensitive adhesive film and can increase the gasoline permeation amount of the pressure-sensitive adhesive film.

[0103] The pressure-sensitive adhesive film according to one embodiment of the present invention is preferably an exterior pressure-sensitive adhesive film for a polyolefin-based resin fuel device.

[0104] The decorative film according to one embodiment of the present invention includes a decorative layer on the other surface opposite to the one surface of the base layer of the pressure-sensitive adhesive film according to one embodiment of the present invention.

[0105] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES

[0106] An embodiment of the present invention will now be described.

[0107] Pressure-sensitive adhesive films of Examples 1 to 7 and Comparative Examples 1 to 9 were produced, and each pressure-sensitive adhesive film was evaluated for gasoline permeation amount, adhesive strength before and after exposure to gasoline, and resistance to gasoline blistering.

[0108] <Material> In this example, the following materials were used:

[0109] [Base material layer] As the substrate layer, the following substrates 1 and 2 were used. Substrate 1: Polyvinyl chloride film (manufactured by Nippon Carbide Industries Co., Ltd., product name "40110Z", thickness 30 μm) Substrate 2: Polyvinyl chloride film (manufactured by Nippon Carbide Industries Co., Ltd., product name "00178M", thickness 70 μm)

[0110] [(Meth)acrylic copolymer (A)] As the (meth)acrylic copolymer (A), butyl acrylate (hereinafter sometimes abbreviated as "BA"), 2-ethylhexyl acrylate (hereinafter sometimes abbreviated as "2EHA", Tg: -70°C) and acrylic acid (hereinafter sometimes abbreviated as "AA") were used as monomers to prepare acrylic copolymers 1 to 5 having the composition ratios shown in Table 1. The solid contents (wt%), glass transition temperatures Tg (°C) and weight average molecular weights Mw (×10 4 ) are also shown in Table 1.

[0111] [Table 1]

[0112] [Tackifying resin (B)] As the tackifier resin (B), the following tackifier resins 1 to 3 were used. Tackifier resin 1: styrene-based synthetic resin (manufactured by Mitsui Chemicals, Inc., product name "FTR6100", solid content 100.0%, "FTR" is a registered trademark of the company) Tackifier resin 2: Terpene phenol-based tackifier resin (manufactured by Yasuhara Chemical Co., Ltd., product name "YS Polystar TH130", solid content 100.0%) Tackifier resin 3: Rosin ester tackifier resin (manufactured by Arakawa Chemical Industries, Ltd., product name "D-125", solid content 100.0%)

[0113] [Crosslinking agent (C)] As the crosslinking agent (C), the following crosslinking agents 1 and 2 were used. Crosslinking agent 1: Tolylene diisocyanate crosslinking agent (manufactured by Tosoh Corporation, product name "Coronate L-45E", solid content 45.0%, "Coronate" is a registered trademark of the company) Crosslinking agent 2: Hexamethylene diisocyanate-based crosslinking agent (manufactured by Asahi Kasei Corporation, product name "Duranate D201", solid content 100.0%, "Duranate" is a registered trademark of the company)

[0114] [Release film] As the release films, the following release films 1 to 3 were used. Release film 1: Matrix separator (Riken Technos Corporation, product name "PE5049A", cross-sectional shape of ridge: trapezoid with height 20 μm, upper side 70 μm, lower side 100 μm; arrangement of ridge: triangular lattice) Release film 2: Matrix separator (manufactured by RIKEN TECHNOS CORPORATION, product name "PE5051A", cross-sectional shape of ridge: trapezoid with height 8 μm, upper side 5 μm, and lower side 20 μm; arrangement of ridge: double hexagonal lattice) Release film 3: Flat separator (manufactured by Lintec Corporation, product name "E-KB", no ridges)

[0115] <Preparation of adhesive film> The pressure-sensitive adhesive films of Examples 1 to 7 and Comparative Examples 1 to 9 were produced as follows.

[0116] Example 1 476.2 parts by weight (100.0 parts by weight in terms of solid content) of acrylic copolymer 1, 15.0 parts by weight (15.0 parts by weight in terms of solid content) of tackifier resin 1, 20.0 parts by weight (20.0 parts by weight in terms of solid content) of tackifier resin 2, and 3.33 parts by weight (1.50 parts by weight in terms of solid content) of crosslinker 1 were kneaded to prepare a pressure-sensitive adhesive composition. The prepared pressure-sensitive adhesive composition was applied to the release-treated surface of release film 1 using an applicator so that the thickness of the pressure-sensitive adhesive composition after drying was 27 μm. The applied pressure-sensitive adhesive composition was heated and dried for 1 minute in an atmosphere of 100 ° C. using a hot air dryer. On the surface of the pressure-sensitive adhesive layer formed by drying the pressure-sensitive adhesive composition, substrate 1 was laminated at 23 ° C. using a rubber roller. The obtained laminate including the substrate layer, pressure-sensitive adhesive layer, and release film 1 was left to stand for 4 days in an atmosphere of 40 ° C. to prepare the pressure-sensitive adhesive film of Example 1.

[0117] Example 2 An adhesive film of Example 2 was produced in the same manner as in Example 1, except that the adhesive composition was applied so that the thickness of the adhesive composition after drying was 35 μm.

[0118] Example 3 The adhesive film of Example 3 was prepared in the same manner as in Example 1, except that 0.20 parts by weight (0.20 parts by weight in terms of solid content) of crosslinking agent 2 was used instead of 3.33 parts by weight (1.50 parts by weight in terms of solid content) of crosslinking agent 1.

[0119] Example 4 The adhesive film of Example 4 was prepared in the same manner as in Example 1, except that 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 3 was used instead of 15.0 parts by weight (15.0 parts by weight in solid content) of tackifier resin 1 and 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 2.

[0120] Example 5 The adhesive film of Example 5 was produced in the same manner as in Example 1, except that 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 3 was used instead of 15.0 parts by weight (15.0 parts by weight in solid content) of tackifier resin 1 and 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 2, and 0.20 parts by weight (0.20 parts by weight in solid content) of crosslinker 2 was used instead of 3.33 parts by weight (1.50 parts by weight in solid content) of crosslinker 1.

[0121] Example 6 The adhesive film of Example 6 was produced in the same manner as in Example 1, except that 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 3 was used instead of 15.0 parts by weight (15.0 parts by weight in solid content) of tackifier resin 1 and 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 2, 0.20 parts by weight (0.20 parts by weight in solid content) of crosslinker 2 was used instead of 3.33 parts by weight (1.50 parts by weight in solid content) of crosslinker 1, and the adhesive composition was applied so that the thickness of the adhesive composition after drying was 35 μm.

[0122] Example 7 An adhesive film of Example 7 was produced in the same manner as in Example 1, except that release film 2 was used instead of release film 1.

[0123] Comparative Example 1 An adhesive film of Comparative Example 1 was produced in the same manner as in Example 1, except that Substrate 2 was used instead of Substrate 1.

[0124] Comparative Example 2 The adhesive film of Comparative Example 2 was prepared in the same manner as in Example 1, except that 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 2 was used instead of 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 1.

[0125] Comparative Example 3 An adhesive film of Comparative Example 3 was prepared in the same manner as in Example 1, except that 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 3 was used instead of 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 1.

[0126] Comparative Example 4 The adhesive film of Comparative Example 4 was prepared in the same manner as in Example 1, except that 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 4 was used instead of 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 1.

[0127] Comparative Example 5 The adhesive film of Comparative Example 5 was prepared in the same manner as in Example 1, except that 312.5 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 5 was used instead of 476.2 parts by weight (100 parts by weight in terms of solid content) of acrylic copolymer 1.

[0128] Comparative Example 6 The adhesive film of Comparative Example 6 was prepared in the same manner as in Example 1, except that 5.0 parts by weight (5.0 parts by weight in solid content) of tackifier resin 1 and 10.0 parts by weight (10.0 parts by weight in solid content) of tackifier resin 2 were used instead of 15.0 parts by weight (15.0 parts by weight in solid content) of tackifier resin 1 and 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 2.

[0129] Comparative Example 7 The adhesive film of Comparative Example 7 was prepared in the same manner as in Example 1, except that 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 1 and 30.0 parts by weight (30.0 parts by weight in solid content) of tackifier resin 2 were used instead of 15.0 parts by weight (15.0 parts by weight in solid content) of tackifier resin 1 and 20.0 parts by weight (20.0 parts by weight in solid content) of tackifier resin 2.

[0130] Comparative Example 8 The adhesive film of Comparative Example 8 was produced in the same manner as in Example 1, except that the adhesive composition was applied so that the thickness of the adhesive composition after drying was 10 μm. In the adhesive film of Comparative Example 8, the groove penetrated the adhesive layer and stopped at the stage where it reached the base layer. Therefore, the actual depth of the groove was 10 μm.

[0131] Comparative Example 9 An adhesive film of Comparative Example 9 was produced in the same manner as in Example 1, except that release film 3 was used instead of release film 1.

[0132] The configurations of the adhesive films of Examples 1 to 7 and Comparative Examples 1 to 9 are shown in Table 2.

[0133] [Table 2]

[0134] <Evaluation of adhesive film> For each of the pressure-sensitive adhesive films of Examples 1 to 7 and Comparative Examples 1 to 9, the amount of gasoline permeation, adhesive strength before and after exposure to gasoline, and resistance to gasoline blistering were evaluated as follows.

[0135] [Evaluation of gasoline permeation amount] 20 mL of unleaded gasoline (made by Idemitsu Showa Shell Co., Ltd.) was added to a moisture permeable cup (made by Imoto Machinery Co., Ltd., product name "Moisture permeable cup (screw fastening type)", a three-point screw fastening type moisture permeable cup with an opening with a diameter of 59.95 mm). The adhesive film of Example 1 from which the release film had been peeled off was attached to the opening of the moisture permeable cup to cover the opening. Immediately after the adhesive film was attached, the change in weight of the moisture permeable cup over time was recorded. The amount of gasoline permeated through the adhesive film of Example 1 was calculated using the following formula (1). Gasoline permeation rate (g / m 2 ·h)=(M1-M2) / (S·T) Formula (1) In formula (1), M1(g) is the weight of the moisture permeable cup immediately after the adhesive film is attached, M2(g) is the weight of the moisture permeable cup after a certain time T(h) has elapsed after the adhesive film is attached, and S(m 2 ) is the opening area of ​​the moisture permeable cup. In this example, T was 4h.

[0136] The gasoline permeation amounts of the PSA films of Examples 2 to 7 and Comparative Examples 1 to 9 were evaluated in the same manner as the PSA film of Example 1. The evaluation results of the gasoline permeation amounts of the PSA films of Examples 1 to 7 and Comparative Examples 1 to 9 are shown in Table 3.

[0137] [Adhesion before exposure to gasoline] A test piece was prepared using the adhesive film of Example 1 as the adhesive film and a polyethylene plate (manufactured by Showa Denko Materials Co., Ltd., product name "EL-N-AN") as the polyolefin resin adherend. Specifically, the adhesive film of Example 1 from which the release film had been peeled off was cut into a size of 25 mm in width and 150 mm in length, and then attached to a polyethylene plate, and left to stand for 48 hours under an atmosphere of 23°C and 50% RH to prepare a test piece. Next, the adhesive strength (N / 25mm) of the test piece was measured in accordance with JIS Z 0237:2009 at a test speed of 300 mm / min and a test angle of 180°.

[0138] The adhesive strength of the PSA films of Examples 2 to 7 and Comparative Examples 1 to 9 before exposure to gasoline was evaluated in the same manner as for the PSA film of Example 1. The evaluation results of the adhesive strength of the PSA films of Examples 1 to 7 and Comparative Examples 1 to 9 before exposure to gasoline are shown in Table 3.

[0139] [Adhesion after exposure to gasoline] A test piece was prepared by using the adhesive film of Example 1 as the adhesive film and a polyethylene plate (manufactured by Showa Denko Materials Co., Ltd., product name "EL-N-AN") as the polyolefin resin adherend. Specifically, the adhesive film of Example 1 from which the release film had been peeled off was cut into a size of 25 mm in width and 150 mm in length, and was attached to a polyethylene plate. The test piece was then left to stand for 48 hours under an atmosphere of 23°C and 50% RH, then for 2 hours under an atmosphere of 23°C, 50% RH and steam of unleaded gasoline (manufactured by Idemitsu Showa Shell Co., Ltd.), and then for 30 minutes under an atmosphere of 23°C and 50% RH to prepare a test piece. Next, the adhesive strength (N / 25mm) of the test piece was measured in accordance with JIS Z 0237:2009 under conditions of a test speed of 300 mm / min and a test angle of 180°.

[0140] The adhesive strength of the adhesive films of Examples 2 to 7 and Comparative Examples 1 to 9 after exposure to gasoline was evaluated in the same manner as for the adhesive film of Example 1. The evaluation results of the adhesive strength of the adhesive films of Examples 1 to 7 and Comparative Examples 1 to 9 after exposure to gasoline are shown in Table 3.

[0141] [Gasoline swelling resistance] The adhesive film of Example 1 from which the release film had been peeled off was attached to the side surface of a polyethylene bottle (manufactured by AS ONE Corporation, product name "Wide-mouthed bottle with inner lid 1L", thickness 1mm) and left to stand for 48 hours under an atmosphere of 23°C and 50% RH. Next, 100 mL of unleaded gasoline (manufactured by Idemitsu Showa Shell Co., Ltd.) was added to the polyethylene bottle, and the bottle was sealed by attaching a lid. The sealed polyethylene bottle was left to stand for 14 days under an atmosphere of 23°C and 50% RH to allow unleaded gasoline to permeate through the side surface of the polyethylene bottle, and the gasoline blister resistance of the attached adhesive film was evaluated. The evaluation of gasoline blister resistance was performed visually using the following evaluation criteria. ◯: No swelling was observed on the surface of the adhesive film. Δ: The surface of the adhesive film appears slightly swollen, but this is within the range that does not cause any practical problems. ×: The surface of the adhesive film appears significantly swollen.

[0142] The pressure-sensitive adhesive films of Examples 2 to 7 and Comparative Examples 1 to 9 were also evaluated for gasoline blister resistance in the same manner as the pressure-sensitive adhesive film of Example 1. The evaluation results for gasoline blister resistance of the pressure-sensitive adhesive films of Examples 1 to 7 and Comparative Examples 1 to 9 are shown in Table 3. If the gasoline blister resistance is ◯ or Δ, it can be judged that there is no practical problem in the use of the pressure-sensitive adhesive film for the exterior of a polyolefin resin fuel device.

[0143] [Table 3]

[0144] <Evaluation Results> The pressure-sensitive adhesive films of Examples 1 to 7 all maintained good adhesion to polyolefin resin adherends even after exposure to gasoline. In addition, the pressure-sensitive adhesive films of Examples 1 to 7 all showed good resistance to gasoline blistering and maintained good appearance even after exposure to gasoline. [Industrial Applicability]

[0145] The present invention can be used as an exterior adhesive film for a polyolefin resin fuel device. [Explanation of symbols]

[0146] 10 Base material layer 20 Adhesive layer 21 Groove 30 Release film 31 Ridge 40 Decorative layer 100 Adhesive Film 101 Adhesive film 200 Decorative Film

Claims

1. A pressure-sensitive adhesive film comprising a base layer and a pressure-sensitive adhesive layer formed on at least one surface of the base layer, The base layer contains a polyvinyl chloride resin, the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a (meth)acrylic copolymer (A), a tackifier resin (B) and a crosslinking agent (C); the pressure-sensitive adhesive layer has a groove on a surface facing away from the base layer, The depth of the groove is smaller than the thickness of the adhesive layer, The gasoline permeation amount of the pressure-sensitive adhesive film under an atmosphere of 23° C. and 50% RH is 15 g / m 2 h or more, the pressure-sensitive adhesive layer has an adhesive strength of 10.0 N / 25 mm or more after being attached to a polyolefin resin adherend and then exposed to gasoline vapor for 2 hours under an atmosphere of 23° C. and 50% RH; The (meth)acrylic copolymer (A) contains a structural unit derived from a (meth)acrylic acid-based monomer (A-1) and an alkyl (meth)acrylate-based monomer (A-2) having a glass transition temperature of −60° C. or lower, the content of the structural unit derived from the (meth)acrylic acid-based monomer (A-1) contained in the (meth)acrylic copolymer (A) is 5 parts by weight or more and 10 parts by weight or less based on 100 parts by weight of the (meth)acrylic copolymer (A); the content of the structural unit derived from the alkyl (meth)acrylate monomer (A-2) contained in the (meth)acrylic copolymer (A) is 20 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the (meth)acrylic copolymer (A); The pressure-sensitive adhesive film, wherein the (meth)acrylic copolymer (A) has a weight average molecular weight of 80×10 4 or more and 150×10 4 or less.

2. The pressure-sensitive adhesive film according to claim 1, wherein the ratio of the depth of the grooves in the pressure-sensitive adhesive layer to the width of the grooves is 2:20 to 10:

20.

3. The adhesive film according to claim 1 or 2, wherein the content of the tackifier resin (B) contained in the adhesive composition is 20 parts by weight or more and 40 parts by weight or less per 100 parts by weight of the (meth)acrylic copolymer (A).

4. 4. The pressure-sensitive adhesive film according to claim 1, which has an adhesive strength to a polyolefin resin adherend before exposure to gasoline vapor of 10.0 N / 25 mm or more.

5. The pressure-sensitive adhesive film according to any one of claims 1 to 4, wherein the pressure-sensitive adhesive layer has a thickness of 20 µm or more and 40 µm or less.

6. The pressure-sensitive adhesive film according to any one of claims 1 to 5, wherein the crosslinking agent (C) is an isocyanate-based crosslinking agent.

7. The pressure-sensitive adhesive film according to any one of claims 1 to 6, wherein the thickness of the base layer is 20 µm or more and 40 µm or less.

8. The adhesive film is an exterior adhesive film for a polyolefin-based resin fuel device. The pressure-sensitive adhesive film according to any one of claims 1 to 7.

9. A decorative film comprising a decorative layer on the other surface opposite to the one surface of the base layer of the adhesive film according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Marking film

    JP1993078626A

  • Adhesive composition and adhesive sheet

    JP2018177902A

  • Adhesive sheet

    JP2019070078A

  • Adhesive film

    JP2019089946A